Stereomicroscopic Evaluation of Dentinal Microcracks After Instrumentation of Curved Canal with Rotary Files in Two Motions - Vasava, Nupur; Modi, Shreya; Joshi, Chintan; Thumar, Sweety; Parmar, Anisha; Jadawala, Kruti (UI Scholars Hub, 2022)
Objective: This study aimed to examine the effects of three distinct file systems with two motion types—rotary and reciprocation—on the development of dentinal microcracks after root canal preparation using a stereomicroscope. Methods: Sixty mandibular molars with a curvature of 30° were decoronated and divided into three groups (Vortex Blue, Mtwo, and ProTaper Next) and two subgroups (rotary and reciprocating motions). The samples were then instrumented with the files, dyed with 1% methylene blue dye, and sectioned horizontally at 3, 6, and 9 mm from the root apex. The dentinal microcracks were inspected using a stereomicroscope at 40× magnification. One-way analysis of variance and post hoc Tukey tests were used to perform statistical analysis. Results: Crack formation was statistically significant at the 6-mm and 9-mm levels from the root apex in both motions (p < 0.05). Among all the file system, Vortex Blue caused the highest dentinal microcracks in both motions at 6 mm from the root apex. Conclusion: The reciprocating motion resulted in fewer dentinal microcracks than the rotary motion. All file systems caused significant dentinal microcracks at the curvature of the root canal during both motions. Dentinal microcrack formation was not significant at the root apex.